Expanding spectrum of anticancer drug, imatinib, in the disorders affecting brain and spinal cord - Kumar, Manish; Kulshrestha, Ritu; Singh, Nirmal; Jaggi, Amteshwar Singh (Pharmacological research, 2019)
[Display omitted] Imatinib is a tyrosine kinase inhibitor and is used as a first line drug in the treatment of Philadelphia-chromosome-positive chronic myeloid leukaemia and gastrointestinal stromal tumors. Being tyrosine kinase inhibitor, imatinib modulates the activities of Abelson gene (c-Abl), Abelson related gene (ARG), platelet-derived growth factor receptor (PDGFR), FMS-like tyrosine kinase 3 (FLT3), lymphocyte-specific protein (Lck), mitogen activated protein kinase (MAPK), amyloid precursor protein intracellular domain (AICD), α-synuclein and the stem-cell factor receptor (c-kit). Studies have shown the role of imatinib in modulating the pathophysiological state of a number of disorders affecting brain and spinal cord such as Alzheimer’s disease, Parkinson’s disease, stroke, multiple sclerosis and spinal cord injury. The present review discusses the role of imatinib in the above described disorders and the possible mechanisms involved in these diseases.